LATE CENOZOIC KINEMATICS OF ACTIVE FAULTS IN THE HOVSGOL BASIN (SOUTHWESTERN FLANK OF THE BAIKAL RIFT) - Arzhannikova A.V.; Parfeevets A.V.; San'kov V.A.; Miroshnichenko A.I. (My University, 2003)
Geometry and Late Cenozoic kinematics of regional and local active faults in the northern and western sides of the Hovsgol basin have been studied through remote sensing and geomorphological and structural field measurements. W-E faults show left-lateral strike slip and a reverse vertical motion, NW faults have a right-lateral and NE faults a left-lateral strike-slip component. This fault geometry corresponds to transpression with NEN principal compression.
Keywords: Geometry of active faults; stress-strain field; Late Cenozoic tectonic activity; Cenozoic; Кайнозой